Evaluation of Vitamin B12 Deficiency Risk in Type 2 Diabetic Patients with Dementia (Journal of Dhaka National Medical College & Hospital, 2026)
Background: Dementia is already a significant health and socioeconomic challenge, even in developing nations such as Bangladesh, as a result of the aging population and various associated risk factors. This study has assessed the likelihood of vitamin B12 deficiency among the elderly diabetic population in Bangladesh. Materials and Methods:The study utilized a cross-sectional observational design. After obtaining informed written consent, data collection was conducted involving 172 respondents or their caregivers through a structured questionnaire derived from the Addenbrooke’s Cognitive Examination (ACE-III) to assess cognitive status. Participants were divided into two groups based on their ACE-III score: Group I for diabetic mellitus (DM) with dementia (score ≤70) and Group II for DM without dementia (score >70). The analysis of data was conducted employing both univariate and multivariate statistical methods, as deemed suitable. Results: In this study,mean± SD of Vitamin B-12 levels showed highly significant difference (p